Jenis dan Daya Bahasa Salah Satu Iklan Rokok Bentoel Tahun 1970-an: Analisis Wacana Pragmatik - Rissari Yayuk (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
Discourse of advertising consists of text and context. This text and context depend on the purpose of the advertising being created. Text and context will show the type and power of an advertising. The problem of this research is, what kind of discourse one of Bentoel advertising of the 1970s? How is the language power one of Bentoel advertising in the 1970s? The purpose of this study is to describe the type of discourse and the language power one of Bentoel advertising the 1970s. This research is a qualitative research with descriptive method. Source of data from within old advertising: blogspot. co. id link. on Friday, February 9, 2018, 04. 22 o’clock. Technique of taking data is library technique and record. Data analysis is content analysis by presenting the description method. Basic theory is study of pragmatic discourse. The results showed that this type of discourse of one of the Bentoel advertising in the 1970s included persuasion. Furthermore, the power of language consists of linguistic, pragmatic, and nonlinguistic aspects.